Do avanafil and zaprinast exert positive effects on bone tissue via the nitric oxide/cyclic guanosine monophosphate/protein kinase-G signaling pathway in rats with ovariectomy-induced osteoporosis? - Zübeyir Huyut; Nuri Bakan; Serkan Yıldırım (Universidade de São Paulo, 2021)
Phosphodiesterase-5 inhibitors (PDE-5Is) exert positive effects on bone healing and mineralization by activation the nitric oxide/cyclic guanosine monophosphate/protein kinase-G (NO/cGMP/PKG) signaling pathway. In this study, the effects of zaprinast and avanafil, two PDE-5Is, on the NO signaling pathway, estrogen levels, selected bone formation and destruction marker levels, whole-body bone mineral density (WB-BMD), right femur trabecular bone thickness (RF-TBT) and epiphyseal bone width, angiogenesis in the bone-marrow, and selected oxidative stress parameter levels were investigated in rats with ovariectomy-induced osteoporosis. Twenty four adult rats (8 months old) were equally divided into four groups. The first group was the sham operated group. Groups 2, 3 and 4 included ovariectomized rats. At six months after ovariectomy, the 3rd and 4th groups were administered 10 mg/kg zaprinast and avanafil daily as a single dose for 60 days, respectively. Increases in the activity of the NO/cGMP/PKG signalling-pathway, C-terminal collagen peptide levels, angiogenesis in the bone marrow, RF-TBT, epiphyseal bone width and WB-BMD were observed compared to the ovariectomized positive control group (OVX), while the pyridinoline and deoxypyridinoline levels were decreased in the OVX+zaprinast and OVX+avanafil groups (p<0.05). The malondialdehyde, ubiquinone10/ubiquinol10 and 8-hydroxy-2-deoxyguanosine/106deoxyguanosine levels were also increased in the ovariectomized groups compared to the sham group (p<0.05). Based on these results, the levels of bone atrophy and some markers of oxidative stress were increased due to acute estrogen deficiency induced by ovariectomy, but zaprinast and avanafil administration significantly prevented these changes